Show that the equation 3x^2 - x^3 + 3 = 0 can be rearranged to give:
x = 3 + 3
----
x^2
x^3 =
Divide by ? = x = 3 + 3
----
x^2
Using Xn+1 = 3 + 3 with x0 = 3.2
----
x^2n
find the values of x1 x2 and x3?
What to the values of x1 x2 and x3 represent?
The represent estimates of a _____ to the equation?
Mathmatics - Reiny, Tuesday, January 3, 2017 at 10:46am
Just re-arrange it ....
3x^2 - x^3 + 3 = 0
-x^3 = -3x^2 - 3
x^3 = 3x^2 + 3
divide both sides by x^2
x = 3 + 3/x^2
let x = 3.2
RS = 3+ 3/10.24 = 3.29296875
sub that into the RS
RS = 3 + 3/(3.2929...)^2 = 3.276659...
new RS = 3.279420685
new RS = 3.278950402
new RS = 3.279030424
new RS = 3.279016806
new RS = 3.279019123
new RS = 3.279018729
new RS = 3.279018796
Hello, Reiny thank you for answering this question. What is the full answer for x2 I need the next 2 digits?
x1= 3.29296875
x2= 3.276659??
x3= 3.27942068
Thanks again. :)